Safety and efficacy of ureteroscopy for urolithiasis in octogenarians. (28th October 2022) - Koterazawa, Shigeki; Kanno, Toru; Takahashi, Toshifumi; Somiya, Shinya; Ito, Katsuhiro; Haitani, Takao; Arakaki, Ryuichiro; Kawase, Norio; Higashi, Yoshihito; Yamada, Hitoshi
Abstract : Objective: To examine the safety and efficacy of ureteroscopy (URS) for urolithiasis in octogenarians, and identify preoperative risk factors for the incidence of postoperative complications. Methods: The patients who underwent URS for urolithiasis were divided into octogenarians and younger patients (age: <80 years), and the groups were compared regarding their clinical characteristics, intraoperative and postoperative complications, and stone‐free rate. The predictors of postoperative complications were evaluated using logistic regression models. Results: A total of 1207 patients were included, 166 in the octogenarian patient group and 1041 in the younger patient group. The proportion of female patients ( p  < 0.001), American Society of Anesthesiologists (ASA) score ( p  < 0.001), rate of preoperative pyelonephritis ( p  < 0.001), and diabetes mellitus ( p  = 0.003) were higher in the octogenarian group. No statistically significant differences were found between the two groups regarding stone size, location, and intraoperative complications. Postoperative complications, which reached a significant difference, were observed in 34 (20.5%) octogenarians and 117 (11.2%) younger patients ( p  = 0.002). However, age itself was not significantly associated with postoperative fever, the most frequent postoperative complication, in multivariate analysis. Female sex, ASA score of ≥3, history of diabetes mellitus, and prolonged operative time (≥120 min) were the significant predictors of fever. The stone‐free rate in the octogenarian group was superior to that in the younger patient group (80.1% vs. 70.6%, respectively; p  = 0.035). Conclusion: Our results suggest that URS for urolithiasis can be safely and effectively applied to octogenarians in selected cases.